THE ESSENCE OF THE MODERN PERIOD AND THE GROWTH OF IMPORTANCE SUSTAINABILITY IN SOCIETY - Pakhrutdinov Shukritdin (American Journals Publishing, 2023)
This article focuses on the analysis and search for new ways and solutions to the crisis situation, which is currently characterized by significant global environmental crises and increased geopolitical tensions. Internal security depends on many internal and external factors, and its effectiveness will be lower without taking into account as many of these factors as possible. The existing threats are of the same nature and consequences for all countries, regardless of their economic and political development. It is recognized that today the theory of universal security has not yet been developed, so each country has its own idea of the threat of resistance from the state. The need for an integrated interstate approach to eliminating.
Keywords: Sustainable society, stability, security, international relations, factors